Effects of long-term conservation agriculture on productivity, soil carbon sequestration and greenhouse gas emissions in rice-wheat systems of the eastern Indo-Gangetic Plains - Riju Pratap Singh; Pratik Sanodiya; Udai Pratap Singh; Harshit Aman; Hitesh Gupta; Rushal Dogra (Biomass and Bioenergy, 2027)

Genome-wide characterization of copy number variations in Nagami Mithun (Bos frontalis) using whole-genome resequencing - Bendangkokba Kichu; Harshit Kumar; Rajkrishna Mondal; Kuluve Chotso; J. K. Chamuah; S. S. Hanah; Girish Patil Shivanagowda (Mammalian Genome, 2026)

EBV-informed multi-omics target prioritization and structure-based drug repurposing reveal potential therapeutic strategies for multiple sclerosis - Nevil M. Lal; Harshit Sajal; Aswin Mohan; Asna R.; Fadiya Fathima; Rajesh Raju; Anuroopa G. Nadh (Functional & Integrative Genomics, 2026)

Nanoparticle-Based PCSK9 Inhibition in Viral Infections: Evaluating Clinical Limitations and Advancing Therapeutic Strategies - Moeen Fuad Dababneh; Bahjat Alhasso; Abdulkareem Shareef; Ashishkumar Kyada; H. Malathi; Laxmidhar Maharana; Dinesh Puri; Harshit Gupta; Nargiza Yarmukhamedova; Hayder Naji Sameer; Ahmed Yaseen; Zainab H. Athab; et al. (Journal of Pharmaceutical Innovation, 2026)

Gas chromatography–mass spectrometry analysis of the secondary metabolites produced by Bacillus paramycoides BOK01 and Microbacterium barkeri BPATH02 and investigation of their antifungal activity against tea pathogens - Pranay Raj; Harshit Kumar Sharma; Venkatesan Selvaraj; Abhay Kumar Pandey (Antonie van Leeuwenhoek, 2026)

Biophysical and biochemical mechanisms underlying resistance in Brassica juncea against mustard aphid, Lipaphis erysimi - Harshit Mishra; Kamal Ravi Sharma; Sameer Kumar Singh (International Journal of Tropical Insect Science, 2026)

Carbon loaded zinc sulfo-oxide (C@Zn(S + O)) composite for efficient and rapid adsorptive removal of Congo red dye from wastewater: optimization, thermodynamics, isothermal and kinetics analysis - Harshit Gupta; Shrawan Kumar; Ria Baliyan; Nahar Singh (Environmental Science and Pollution Research, 2026)

Pathological and molecular characterization identified Muyocopron laterale as a new pathogen causing brown leaf spot disease of tea in India - Harshit Kumar Sharma; Pranay Raj; Sajeewa S. N. Maharachchikumbura; Abhay Kumar Pandey (Journal of Plant Diseases and Protection, 2026)

Effects of heading back on leaf nutrients, flowering, physiological and fruit-related traits in mango (Mangifera indica L.) cv. Amrapali - Harshit Kumar; Manish Srivastav; Kanhaiya Singh; A. Nagaraja; S. Gopala Krishnan; Pandey Rakesh; Shruti Shethi; V. K. Sharma; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena (Vegetos, 2026)

Nonlinear assessment of progressive collapse in irregular buildings triggered by pulse-type near-field earthquakes - Harshit Jain; Mohit Bhandari (Bulletin of Earthquake Engineering, 2026)

Effect of Tree Age on Leaf Nutrient, Flowering, Physiological and Fruit-Related Traits in ‘Amrapali’ Mango (Mangifera indica L.) Under an Intensive Planting System - Harshit Kumar; Manish Srivastav; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena; Kanhaiya Singh; A. Nagaraja; Gopala Krishnan S.; Rakesh Pandey; Shruti Shethi; V. K. Sharma (Applied Fruit Science, 2026)

Record of glacial overriding driven soft-sediment deformation structures (SSDS) from Late Paleozoic glaciomarine Talchir Formation, Son Valley Basin: Implications on ice-sheet dynamics and Lower Gondwana paleogeography - Harshit Varshney; Biplab Bhattacharya (Journal of Earth System Science, 2026)

A comprehensive review on Mithun (Bos frontalis): a keystone species in sustainable livelihoods of the eastern Himalayas and Indo-Burma region - Youngmei Arolim; Harshit Kumar; Sapunii Stephen Hanah; Tapas Kumar Biswas; Kathiravan Periasamy; Kuluve Chotso; Jayanta Kumar Chamuah; Girish Patil Shivanagowda (Tropical Animal Health and Production, 2026)

AI-driven generative framework integrating ML-QSAR and fragment learning for isoform-selective PI3K inhibitor design - Harshit Sajal; Aswin Mohan; Rajesh Raju; Anuroopa G. Nadh (Molecular Diversity, 2026)

Inter-hemispheric climate linkages and monsoonal controls on the Arabian Sea surface temperatures - Harshit Singh; Arun Deo Singh; Aindabi Maitra; Bandan Kumar; Shubham Tripathi; Pradyumna Singh; Shivranjan Kumar Bharti (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Zinc Peroxide-based Carbon Composite for the Removal of Highly Toxic Insecticide Acetamiprid from Water - Shrawan Kumar; Harshit Gupta; Arvind Gautam; Nahar Singh (Water, Air, & Soil Pollution, 2026)

Exposure assessment of PM2.5 in different transport modes for a unique city layout plan in Kanpur City of India - Harshit Verma; Dipteek Parmar; Rajiv Ganguly (Air Quality, Atmosphere & Health, 2026)

Reimagining urban air-quality governance: A systems-thinking framework - Harshit Gujral; Om Damani; Anshul Agarwal; Christoph Becker; Meredith Franklin; Teresa Kramarz; Ronak Sutaria; Sagnik Dey; Steve Easterbrook (Science of The Total Environment, 2026)

Development of a visual assay for Mithun (Bos frontalis) meat authentication using polymerase spiral reaction (PSR) - Moon Moon Mech; Hanumant Singh Rathore; Arockiasamy Arun Prince Milton; Nagappa Karabasanavar; Kandhan Srinivas; Sabia Khan; Zakir Hussain; Vikram Ramesh; Harshit Kumar; Samir Das; Sandeep Ghatak; Girish Patil Shivanagowda (Food Control, 2026)

Role of CRISPR in bioremediation of heavy metal(loid): a breakthrough in environmental biotechnology - Harshit Mangal; Shivangi Mathur; Sunil Kumar; Anurag Chaurasia; Rajiv Ranjan (World Journal of Microbiology and Biotechnology, 2026)

How spatiotemporal urban expansion shapes heat trends in coastal megacities: Developed vs. developing nations - Dyutisree Halder; Harshit; Rahul Dev Garg (Urban Climate, 2025)

Influence of homocysteine on regulating immunothrombosis: mechanisms and therapeutic potential in management of infections - Aswathy S Nair; Lloyd Tauro; Harshit B Joshi; Arnab Makhal; Teddy Sobczak; Julien Goret; Antoine Dewitte; Srinivas Kaveri; Harinath Chakrapani; Maria Mamani Matsuda; Manjunath B Joshi (Inflammation Research, 2025)
Mechanisms controlling innate immune responses and coagulation are interdependent, evolutionarily entangled and make a complex network to form immuno-thrombosis axis which is an integral part of host-defence response. During infections, immunothrombosis generates intravascular scaffold enabling recognition, trap and destruction of pathogens facilitating tissue integrity. However, the accompanying dysregulation fosters into pathologies associated with thrombosis and regulates severity, morbidity and mortality in infections. Several extrinsic and intrinsic factors such as (epi)genetic mechanisms, age, metabolism and lifestyle regulate immunothrombosis during infections. Mounting evidence demonstrates that homocysteine, a metabolic intermediate of methionine synthesis pathway activate cells participating in immuno-thrombosis such as neutrophils, platelets, monocytes and endothelial cells. Interestingly, multiple infections are significantly associated with perturbed homocysteine metabolism. In the present review, we describe mechanistic insights into how homocysteine drives immuno-thrombotic crosstalk that generate a vicious cycle of inflammation and coagulation that fuels organ failure during infections with an emphasis on sepsis, COVID-19, and other infectious diseases caused by parasites, viral, and bacterial pathogens. Subsequently, we discuss therapeutic strategies targeting homocysteine metabolism that may improve clinical outcomes in infections.

First report of Agroathelia rolfsii causing stem rot on Zamioculcas zamiifolia (ZZ plant) in India - Sushanti Thokchom; Akoijam Ratankumar Singh; Mayur R. Thesiya; Harshang Talaviya; Ronak Mangroliya; Chandni Mori; Harshit Chavda (Indian Phytopathology, 2025)

Impact of Micronutrients on Flowering, Yield, and Fruit Quality Attributes of Strawberry (Fragaria × ananassa Duch) cv. Camarosa Under Open Field Conditions - Yogendra Singh; Govind Gupta; Ujwal Virkhare; Mukul Kumar; Prajwal Nimbulkar; Suman Kumari; Yogita Chouhan; Harshit Jangid; Suresh Chandra Gurjar; Om Prakash Lodha; Deepak Kher (Applied Fruit Science, 2025)

Advancing agroforestry research in the Indian Himalayas: a systematic review of knowledge trends, research gaps, and circular economy pathways - Harshit Pant; Paras Upadhyaya; Paromita Ghosh (Agroforestry Systems, 2025)

First report of Curvularia alcornii causing leaf blight disease on tea (Camellia sinensis) in North Bengal, India - Abhay Kumar Pandey; Harshit K. Sharma; Abhishek Kumar; Pranab Dutta (Journal of Plant Pathology, 2025)

A Hybrid Approach Combining Dual-Energy and Inpainting Methods for Metal Artifact Reduction in Dentomaxillofacial CBCT: A Proof-of-Concept Phantom Study - Dinidu Jayakody; Harshit Agrawal; Ella Räinä; Annina Sipola; Ritva Näpänkangas; Sampo Ylisiurua; Miika T. Nieminen; Mikael Brix (Annals of Biomedical Engineering, 2025)
Purpose Image inaccuracies and distortions are amplified in cone-beam computed tomography (CBCT), with beam hardening and metal artifacts being particularly pronounced, thereby complicating diagnostic interpretation. An approach, combining dual-energy CBCT based projection-domain material decomposition with virtual monochromatic imaging (VMI) technique, was leveraged to mitigate beam hardening artifacts originating from dental restorative and prosthetic materials on a diagnostic CBCT scanner in a phantom setting. Methods Severe artifact-causing dental restorative and prosthetic materials were identified from the literature and six of them were selected for the study. Six different phantoms were developed using selected materials, and 3D-printed cylindrical molds filled with gelatine. Three different tube voltages, such as 80 kilovoltage (kV), 100 kV, 120 kV were selected for scanning and the phantoms were scanned using a commercial CBCT scanner (Viso G7, Planmeca Oy., Helsinki, Finland). A custom-developed material decomposition algorithm, based on polychromatic projection domain modeling, was employed to separate the dual-energy data into water and iron basis materials. VMIs were then synthesized at 200 keV using the decomposed data. For comparison, the 100 kV acquisition (routine protocol) with and without the vendor’s inpainting-based MAR algorithm was used to assess VMI techniques’ performance for artifact reduction. Results Both subjectively and quantitatively, the VMI technique offered better image quality than the routine 100 kV protocol. Further, combining the VMI technique with an inpainting-based MAR algorithm offered superior artifact reduction ( p Conclusions The proposed VMI + MAR technique offered superior artifact reduction compared to a commercial MAR algorithm.

Changes in the upper water-column structure of the eastern equatorial Indian Ocean during 12.8–4.7 ka - Pradyumna Singh; Arun Deo Singh; Shubham Tripathi; Harshit Singh; Abhayanand Singh Maurya; Sushant Suresh Naik; Rakesh Kumar (Quaternary International, 2025)

Effect of ventilation settings on the in-car PM concentrations and the associated health risks in Kanpur, India - Harshit Verma; Dipteek Parmar; Rajiv Ganguly (Atmospheric Pollution Research, 2025)

Mapping grain crop sowing date in smallholder systems using optical imagery - Victor Hugo Rohden Prudente; Mariana Garcia-Medina; Vijesh Krishna; Michael Euler; Nishan Bhattarai; Amy M. Lerner; Andrew James McDonald; Sonam Sherpa; Harshit Rajan; Anton Urfels; Cleverton Tiago Carneiro de Santana; Meha Jain (Remote Sensing Applications: Society and Environment, 2025)

Pathways to enhanced microscale coastal flood risk assessment amid changing climate - Avinash Kaur; Harshit Sosan Lakra; Rajib Shaw; Sameer Ali (Natural Hazards, 2025)

An innovative machine learning-based QSAR approach for prediction and structural analysis of novel/repurposed acid ceramidase (ASAH1) inhibitors for glioblastoma therapy - Harshit Sajal; Seema Mishra (Molecular Diversity, 2025)

Harnessing Machine Learning and Optimization Techniques for Identifying Risk Factor of Sleep Apnea by Exploring Sleep Health and Lifestyle Dataset - Mubashir Khan; Yashpal Singh; Harshit Bhardwaj (Sleep and Vigilance, 2025)

Synergistic effect of molybdenum and Rhizobium on growth and yield of vegetable cowpea (Vigna unguiculata (L.) Walp.) - Monu Kumari; Nitin B. Patel; Kapil Dev Ameta; Akshay Kumar Yogi; Harshit Kumar; Ayushi Jain (Vegetos, 2025)

Pesticide-driven antimicrobial resistance in water bodies: insights on environmental concerns, health implications and mitigation strategies - Vishwajeet Sonkar; Harshit Devtalla; Shakti Kumar (Environmental Geochemistry and Health, 2025)

Network analysis of ground-level ozone: Implications for environmental policy and air quality management - Harshit Gujral; Somya Jain; Adwitiya Sinha (Environmental Modelling & Software, 2025)

Phylogenetic reassessment and epitypification of Exobasidium vexans causing blister blight of tea - Ganga Devi Sinniah; Dalawellage Chanuka Madushanka Kulatunga; Abhay Kumar Pandey; Harshit Kumar Sharma; Nelanka Priyadarshani Colombage; Dhanushka Udayanga (Australasian Plant Pathology, 2025)

A comprehensive review on the treatment of pharmaceutically active compounds using moving bed biofilm reactor: A systematic meta-analysis coupled with meta-neural approach - Saswata Sahu; Pranjal Ghosal; Harshit Patel; Partha Sarathi Ghosal (Journal of Environmental Management, 2025)

Emerging evidence for the impact of Electric Vehicle sales on childhood asthma: Can ZEV mandates help? - Harshit Gujral; Meredith Franklin; Steve Easterbrook (Environmental Research, 2025)

A comprehensive review on desalination using membrane-based technologies in India: A bibliometric analysis and meta-analysis - Pranjal Ghosal; Saswata Sahu; Harshit Patel; Partha Sarathi Ghosal (Desalination, 2025)

Computational investigation of antiviral peptide interactions with Mpox DNA polymerase - Harshit Tiwari; Ashal Ilyas; Pankaj Kumar Rai; Shashank Upadhyay; Subhomoi Borkotoky (In Silico Pharmacology, 2025)

A method for automatic verification of thunderstorm nowcasts - Soma Sen Roy; Kavita Navria; Anshul Chauhan; Pradeep Sharma; Shikha Verma; Harshit Shukla; K C Saikrishnan; Sankar Nath; M Mohapatra (Journal of Earth System Science, 2024)

Trichoderma harzianum TIND02 upregulates the expression of pathogenesis-related genes and enzymes and enhances gray blight resistance in tea - Abhay K. Pandey; Shivanand Yadav; Mahesh K. Samota; Harshit K. Sharma; Somnath Roy (Pesticide Biochemistry and Physiology, 2024)

A new canker on Camellia sinensis (L.) Kuntze associated with Diaporthe longicolla and Lasiodiplodia theobromae in India - Abhay K. Pandey; Harshit K. Sharma; Shivanand Yadav; Somnath Roy; Azariah Babu (Physiological and Molecular Plant Pathology, 2024)

Adsorption and storage of hydrogen- A computational model approach - Harshit Mittal; Omkar Singh Kushwaha; Mallikarjuna Nadagouda; Gurumurthy Hegde; Stephen Allen; Tejraj M. Aminabhavi (Environmental Research, 2024)

A comprehensive review on the pharmacological role of gut microbiome in neurodegenerative disorders: potential therapeutic targets - Namra Aziz; Pranay Wal; Aman Patel; Harshit Prajapati (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Cell membrane proteome analysis in HEK293T cells challenged with α-synuclein amyloids - Harshit Vaish; Shemin Mansuri; Aanchal Jain; Swasti Raychaudhuri (Journal of Biosciences, 2024)

Molecular delineation and genetic diversity of Fusarium species complex causing tea dieback in India and their sensitivity to fungicides - Abhay K. Pandey; Manjunath Hubballi; Harshit K. Sharma; R. Ramesh; Somnath Roy; K. Dinesh; Azariah Babu (Crop Protection, 2024)

Genetic parameters of body weight traits in Mithun (Bos frontalis) using animal model - Harshit Kumar; Ashish Yadav; Sapunii Stephen Hanah; L. Sunitibala Devi; Kobu Khate; Girish P.S. (Tropical Animal Health and Production, 2024)

A clean and sustainable method for recycling of lithium from spent lithium iron phosphate battery powder by using formic acid and oxygen - Tianyu Zhao; Harshit Mahandra; Yeonuk Choi; Weilun Li; Zhifei Zhang; Zhongwei Zhao; Ailiang Chen (Science of The Total Environment, 2024)

An overview on the life cycle of lithium iron phosphate: synthesis, modification, application, and recycling - Tianyu Zhao; Harshit Mahandra; Rajashekhar Marthi; Xiaobo Ji; Wenqing Zhao; Sujin Chae; Michael Traversy; Weilun Li; Fan Yu; Lin Li; Yeonuk Choi; Ahmad Ghahreman; et al. (Chemical Engineering Journal, 2024)

Analytical Estimation of Strain Energy Accumulation in Retreating Longwall Mining and Sensitivity Analysis Using the Orthogonal Testing Method - Harshit Agrawal; Sevket Durucan; Wenzhuo Cao; Wu Cai (Rock Mechanics and Rock Engineering, 2024)
Excessive strain energy accumulation in the coal seam is one of the essential conditions for rockbursts to occur. It is imperative to understand the parameters that affect the strain energy accumulation in retreating longwall mining to optimise the design and minimise rockbursts occurrences. In this paper, new analytical models were developed to calculate the strain energy accumulation considering the current state-of-the-art longwall machinery being used in the industry. Seven parameters, i.e., mining depth, length of the cantilever roof, coal seam thickness, thickness of the immediate roof, Young’s modulus of coal and the roof, and Poisson’s ratio of the coal seam, were identified as the parameters affecting the strain energy accumulation. A detailed statistical analysis of the parameters was conducted using the orthogonal testing method, which revealed that mining depth, Young's modulus of coal and the coal seam thickness significantly influence the strain energy accumulation within a 99% confidence interval.

Evaluation of the sorption/desorption processes of pesticides in biodegradable mulch films used in agriculture - Harshit Sahai; María Dolores Hernando; María Jesús Martínez Bueno; Ana M. Aguilera del Real; Amadeo R. Fernández- Alba (Chemosphere, 2024)

Bottom-up approach to explore alpha-amylase assisted membrane remodelling - Harshit Kumar; Sayar Mandal; Reena Yadav; Suhasi Gupta; Hemraj Meena; Mayur Kadu; Rajni Kudawla; Pratibha Sharma; Indu Pal Kaur; Subhabrata Maiti; John H. Ipsen; Tripta Bhatia (Chemistry and Physics of Lipids, 2024)

Techno-environmental analysis to valorize the secondary energy resources from refuse-derived fuel-based waste to energy plant - Harshit Patel; Tejaswini MSSR; Gopa Nandikes; Nidhi Pandey; Debleena Bhattacharya; Pankaj Pathak (Environmental Science and Pollution Research, 2024)

Quantification of nanoplastic uptake and distribution in the root, stem and leaves of the edible herb Lepidum sativum - Harshit Sahai; María Jesús Martínez Bueno; María del Mar Gómez-Ramos; Amadeo R. Fernández-Alba; María Dolores Hernando (Science of The Total Environment, 2024)

Reversing the damage: ecological restoration of polluted water bodies affected by pollutants due to anthropogenic activities - Harshit Chawla; Santosh Kumar Singh; Anil Kumar Haritash (Environmental Science and Pollution Research, 2023)

Advancements in open-source photogrammetry with a point cloud standpoint - Harshit; Kamal Jain; Sisi Zlatanova (Applied Geomatics, 2023)

Relative extents, mechanisms, and kinetics of fluoride removal from synthetic groundwater by prevalent sorbents - Aravinth Siva Subramaniam Ekamparam; Harshit Khaitan; Vishakha Nimesh; Abhas Singh (Chemosphere, 2023)

Direct selective leaching of lithium from industrial-grade black mass of waste lithium-ion batteries containing LiFePO4 cathodes - Tianyu Zhao; Rajashekhar Marthi; Harshit Mahandra; Sujin Chae; Michael Traversy; Farzaneh Sadri; Yeonuk Choi; Ahmad Ghahreman (Waste Management, 2023)

Application of Phanerochaete chrysosporium for enhancing gold recovery via bio-oxidation of refractory sulfidic ores in a circumneutral environment - Guillermo Hein; Harshit Mahandra; Ahmad Ghahreman (Process Safety and Environmental Protection, 2023)

Rockburst and Gas Outburst Forecasting using a Probabilistic Risk Assessment Framework in Longwall Top Coal Caving Faces - Harshit Agrawal; Sevket Durucan; Wenzhuo Cao; Anna Korre; Ji-Quan Shi (Rock Mechanics and Rock Engineering, 2023)
A probabilistic risk assessment framework was developed to mathematically represent the complex engineering phenomena of rock bursts and gas outbursts for a heterogeneous coal seam. An innovative object-based non-conditional simulation approach was used to distribute lithological heterogeneity present in the coal seam to respect their geological origin. The changing mining conditions during longwall top coal caving mining (LTCC) were extracted from a coupled numerical model to provide statistically sufficient data for probabilistic analysis. The complex interdependencies among abutment stress, pore pressure, the volume of total gas emission and incremental energy release rate, their stochastic variations and uncertainty were realistically implemented in the GoldSim software, and 100,000 equally likely scenarios were simulated using the Monte Carlo method to determine the probability of rock bursts and gas outbursts. The results obtained from the analysis incorporate the variability in mechanical, elastic and reservoir properties of coal due to lithological heterogeneity and result in the probability of the occurrence of rock bursts, coal and gas outbursts, and safe mining conditions. The framework realistically represents the complex mining environment, is resilient and results are reliable. The framework is generic and can be suitably modified to be used in different underground mining scenarios, overcoming the limitations of earlier empirical indices used.

First report of whole genome sequence of septicemic Pasteurella multocida serovar B:2 ‘Soron’ strain isolated from swine - Harshit Verma; Mayank Rawat; Rishendra Verma; Ravi Gandham; Ashok Kumar Tiwari; Raja Ishaq Nabi Khan; Manas Ranjan Praharaj; Emily Smith (Brazilian Journal of Microbiology, 2023)

Potential utilization of fungi in biomining as biological engines for the alteration of sulfide and carbon matrices - Guillermo Hein; Harshit Mahandra; Ahmad Ghahreman (Reviews in Environmental Science and Bio/Technology, 2023)

Exploring sorption of pesticides and PAHs in microplastics derived from plastic mulch films used in modern agriculture - Harshit Sahai; Mar García Valverde; María Murcia Morales; María Dolores Hernando; Ana M. Aguilera del Real; A.R. Fernández- Alba (Chemosphere, 2023)

A novel neutrophilic bacteria based process for selective LiFePO4 cathode recycling - Harshit Mahandra; Guillermo Hein; Fariborz Faraji; Ahmad Ghahreman (Resources, Conservation and Recycling, 2023)

Air pollution prediction system using XRSTH-LSTM algorithm - Harshit Srivastava; Santos Kumar Das (Environmental Science and Pollution Research, 2023)

Inflammation and vascular remodeling in COVID-19 hearts - Christopher Werlein; Maximilian Ackermann; Helge Stark; Harshit R. Shah; Alexandar Tzankov; Jasmin Dinonne Haslbauer; Saskia von Stillfried; Roman David Bülow; Ali El-Armouche; Stephan Kuenzel; Jan Lukas Robertus; Marius Reichardt; et al. (Angiogenesis, 2023)
A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A ( n = 16), lymphocytic non-influenza myocarditis cases ( n = 8), and non-inflamed heart tissue ( n = 9). We employed conventional histopathology, multiplexed immunohistochemistry (MPX), microvascular corrosion casting, scanning electron microscopy, X-ray phase-contrast tomography using synchrotron radiation, and direct multiplexed measurements of gene expression, to assess morphological and molecular changes holistically. Based on histopathology, none of the COVID-19 samples fulfilled the established diagnostic criteria of viral myocarditis. However, quantification via MPX showed a significant increase in perivascular CD11b/TIE2 + —macrophages in COVID-19 over time, which was not observed in influenza or non-SARS-CoV-2 viral myocarditis patients. Ultrastructurally, a significant increase in intussusceptive angiogenesis as well as multifocal thrombi, inapparent in conventional morphological analysis, could be demonstrated. In line with this, on a molecular level, COVID-19 hearts displayed a distinct expression pattern of genes primarily coding for factors involved in angiogenesis and epithelial-mesenchymal transition (EMT), changes not seen in any of the other patient groups. We conclude that cardiac involvement in COVID-19 is an angiocentric macrophage-driven inflammatory process, distinct from classical anti-viral inflammatory responses, and substantially underappreciated by conventional histopathologic analysis. For the first time, we have observed intussusceptive angiogenesis in cardiac tissue, which we previously identified as the linchpin of vascular remodeling in COVID-19 pneumonia, as a pathognomic sign in affected hearts. Moreover, we identified CD11b + /TIE2 + macrophages as the drivers of intussusceptive angiogenesis and set forward a putative model for the molecular regulation of vascular alterations.

Selective gold recovery from pregnant thiocyanate leach solution using ion exchange resins - Atefeh Azizitorghabeh; Harshit Mahandra; Juliana Ramsay; Ahmad Ghahreman (Hydrometallurgy, 2023)

Centennial-millennial scale ocean-climate variability in the northeastern Atlantic across the last three terminations - Harshit Singh; Arun Deo Singh; Ravi Tripathi; Pradyumna Singh; Komal Verma; Antje H.L. Voelker; David A. Hodell (Global and Planetary Change, 2023)

Numerical Methodology to Evaluate Trackability and Pushability of PTCA Balloon Catheter - Martin L. Sirivella; Ganesh B. Rahinj; Harshit S. Chauhan; Menta V. Satyanarayana; Laxminarayanan Ramanan (Cardiovascular Engineering and Technology, 2023)

Urban flood resilience: mapping knowledge, trends and structure through bibliometric analysis - Naveen Prashar; Harshit Sosan Lakra; Harsimran Kaur; Rajib shaw (Environment, Development and Sustainability, 2023)

Anaerobic digestion as a tool to manage eutrophication and associated greenhouse gas emission - Amit Singh; Mohit Singh Rana; Harshit Tiwari; Manoj Kumar; Sarthak Saxena; Vishal Anand; Sanjeev Kumar Prajapati (Science of The Total Environment, 2023)

Allelopathic effect of benzoic acid (hydroponics root exudate) on microalgae growth - Harshit Tiwari; Sanjeev Kumar Prajapati (Environmental Research, 2023)

PhenoBot: an automated system for leaf area analysis using deep learning - Grant A. Richardson; Harshit K. Lohani; Chaitanyam Potnuru; Leela Prasad Donepudi; Praveen Pankajakshan (Planta, 2023)

Biogenesis of thiosulfate in microorganisms and its applications for sustainable metal extraction - James McNeice; Harshit Mahandra; Ahmad Ghahreman (Reviews in Environmental Science and Bio/Technology, 2022)

Eco‐physiological portrait of a novel Pseudomonas sp. CSV86 : an ideal host/candidate for metabolic engineering and bioremediation - Prashant S. Phale; Balaram Mohapatra; Harshit Malhotra; Bhavik A. Shah (Environmental Microbiology, 2022)
Summary Pseudomonas sp. CSV86, an Indian soil isolate, degrades wide range of aromatic compounds like naphthalene, benzoate and phenylpropanoids, amongst others. Isolate displays the unique and novel property of preferential utilization of aromatics over glucose and co‐metabolizes them with organic acids. Interestingly, as compared to other Pseudomonads, strain CSV86 harbours only high‐affinity glucokinase pathway (and absence of low‐affinity oxidative route) for glucose metabolism. Such lack of gluconate loop might be responsible for the novel phenotype of preferential utilization of aromatics. The genome analysis and comparative functional mining indicated a large genome (6.79 Mb) with significant enrichment of regulators, transporters as well as presence of various secondary metabolite production clusters, suggesting its eco‐physiological and metabolic versatility. Strain harbours various integrative conjugative elements (ICEs) and genomic islands, probably acquired through horizontal gene transfer events, leading to genome mosaicity and plasticity. Naphthalene degradation genes are arranged as regulonic clusters and found to be part of ICE CSV86 nah . Various eco‐physiological properties and absence of major pathogenicity and virulence factors (risk group‐1) in CSV86 suggest it to be an ideal candidate for bioremediation. Further, strain can serve as an ideal chassis for metabolic engineering to degrade various xenobiotics preferentially over simple carbon sources for efficient remediation.

Unraveling genetic admixture in the Indian crossbred cattle by different approaches using Bovine 50K BeadChip - Dhan Pal; Manjit Panigrahi; Supriya Chhotaray; Harshit Kumar; Sonali Sonejita Nayak; Divya Rajawat; Subhashree Parida; G. K. Gaur; Triveni Dutt; Bharat Bhushan (Tropical Animal Health and Production, 2022)

Numerical Analysis for Non-Uniformity of Balloon-Expandable Stent Deployment Driven by Dogboning and Foreshortening - Ganesh B. Rahinj; Harshit S. Chauhan; Martin L. Sirivella; Menta V. Satyanarayana; Laxminarayanan Ramanan (Cardiovascular Engineering and Technology, 2022)

Comparison of TiO2 catalysis and Fenton’s treatment for rapid degradation of Remazol Red Dye in textile industry effluent - Harsh Pipil; Shivani Yadav; Harshit Chawla; Sonam Taneja; Manisha Verma; Nimisha Singla; A. K. Haritash (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

An integrated approach for modeling uncertainty in human health risk assessment - Harshit Mishra; Jitendra Singh; Subhankar Karmakar; Rakesh Kumar (Environmental Science and Pollution Research, 2021)

Benthic Foraminiferal Response to the Millennial-Scale Variations in Monsoon-Driven Productivity and Deep-Water Oxygenation in the Western Bay of Bengal During the Last 45 ka - Komal Verma; Harshit Singh; Arun Deo Singh; Pradyumna Singh; Rajeev Kumar Satpathy; Pothuri Divakar Naidu (Frontiers in Marine Science, 2021)
In this study, we presented a high-resolution benthic foraminiferal assemblage record from the western Bay of Bengal (BoB) (off Krishna–Godavari Basin) showing millennial-scale variations during the last 45 ka. We studied temporal variations in benthic foraminiferal assemblages (relative abundances of ecologically sensitive groups/species, microhabitat categories, and morphogroups) to infer past changes in sea bottom environment and to understand how monsoon induced primary productivity-driven organic matter export flux and externally sourced deep-water masses impacted the deep-sea environment at the core site. Our records reveal a strong coupling between surface productivity and benthic environment on glacial/interglacial and millennial scale in concert with Northern Hemisphere climate events. Faunal data suggest a relatively oxic environment when the organic matter flux to the sea floor was low due to low primary production during intensified summer monsoon attributing surface water stratification and less nutrient availability in the mixed layer. Furthermore, records of oxygen-sensitive benthic taxa (low-oxygen vs. high-oxygen benthics) indicate that changes in deep-water circulation combined with the primary productivity-driven organic matter flux modulated the sea bottom oxygen condition over the last 45 ka. We suggest that the bottom water at the core site was well-ventilated during the Holocene (except for the period since 3 ka) compared with the late glacial period. At the millennial timescale, our faunal proxy records suggest relatively oxygen-poor condition at the sea floor during the intervals corresponding to the cold stadials and North Atlantic Heinrich events (H1, H2, H3, and H4) compared with the Dansgaard/Oeschger (D-O) warm interstadials. The study further reveals oxygen-poor bottom waters during the last glacial maximum (LGM, 19–22 ka) which is more pronounced during 21–22 ka. A major shift in sea bottom condition from an oxygenated bottom water during the warm Bølling–Allerød (B/A) (between 13 and 15 ka) to the oxygen-depleted condition during the cold Younger Dryas (YD) period (between 10.5 and 13 ka) is noticed. It is likely that the enhanced inflow of North Atlantic Deep Water (NADW) to BoB would have ventilated bottom waters at the core site during the Holocene, B/A event, and probably during the D-O interstadials of marine isotope stage (MIS) 3.

Evaluation of precipitation datasets available on Google earth engine over India - Saket Dubey; Harshit Gupta; Manish Kumar Goyal; Nitin Joshi (International Journal of Climatology, 2021)
Monthly mean precipitation estimates of seven products (TerraClimate, TRMM, CHIRPS, PERSIANN‐CDR, GPM‐IMERG, ERA5 and CFSR) available on Google earth engine (GEE) are evaluated against gridded gauge‐based precipitation product available from Indian Meteorological Department (IMD) for their skills and presence of systematic biases (during 2001–2018). All these products represent the climatological features reasonably well. Presence of systematic biases in these products is also observed from their evaluation. Biases across the periphery of the country are relatively on the higher side in comparison to the central regions. The magnitude of spatial variability is represented better for winter precipitation in comparison to summer precipitation. During both winter and summer, ensemble mean of various products outperforms individual products in terms of both RMSE and correlation. Performance of these products is also assessed across various Indian states, elevation bands and climate zones. The ability of these products to represent the seasonality was observed to be highest for the states with mid‐ranged peaks (10–20 mm·day −1 ) which tend to decrease with both increasing and decreasing peaks. Ability of the precipitation products to resemble the annual cycle does not vary with the amount of precipitation, although individual disparity among the products exists. Additionally, an alternative approach for data evaluation using Multiple Triple Collocation (MTC) was performed for the period 2001–2015 using an additional dataset obtained from soil‐moisture‐based rainfall estimates (SM2RAIN). Results from MTC convey that ERA5 performs relatively poor in comparison to the other products for central India followed by CFSR. In brief, the comprehensive evaluation of precipitation products reported herein will act a valuable reference for the researchers as well as decision makers to select the optimal product for their intended application and will inform the users about the various uncertainties in the foundations and specification of these products.

Analysis of Survey Approach Using UAV Images and Lidar for a Chimney Study - Harshit; Kamal Jain; Vaishnavi Mishra (Journal of the Indian Society of Remote Sensing, 2021)

Understanding Spatio-temporal Pattern of Grassland Phenology in the western Indian Himalayan State - Harshit Rajan; C. Jeganathan (Journal of the Indian Society of Remote Sensing, 2019)

A long-term comparative assessment of human health risk to leachate-contaminated groundwater from heavy metal with different liner systems - Harshit Mishra; Subhankar Karmakar; Rakesh Kumar; Praneeth Kadambala (Environmental Science and Pollution Research, 2018)

A framework for assessment and characterisation of municipal solid waste landfill leachate: an application to the Turbhe landfill, Navi Mumbai, India - Harshit Mishra; Merwan Rathod; Subhankar Karmakar; Rakesh Kumar (Environmental Monitoring and Assessment, 2016)